A homozygous UBA5 pathogenic variant causes a fatal congenital neuropathy. Issue 12 (16th March 2020) - Cabrera-Serrano, Macarena; Coote, David Joseph; Azmanov, Dimitar; Goullee, Hayley; Andersen, Erik; McLean, Catriona; Davis, Mark; Ishimura, Ryosuke; Stark, Zornitza; Vallat, Jean-Michel; Komatsu, Masaaki; Kornberg, Andrew; et al.
Abstract : Background: UBA5 is the activating enzyme of UFM1 in the ufmylation post-translational modification system. Different neurological phenotypes have been associated with UBA5 pathogenic variants including epilepsy, intellectual disability, movement disorders and ataxia. Methods and results: We describe a large multigenerational consanguineous family presenting with a severe congenital neuropathy causing early death in infancy. Whole exome sequencing and linkage analysis identified a novel homozygous UBA5 NM_024818.3 c.31C>T (p.Arg11Trp) mutation. Protein expression assays in mouse tissue showed similar levels of UBA5 in peripheral nerves to the central nervous system. CRISPR-Cas9 edited HEK (human embrionic kidney) cells homozygous for the UBA5 p.Arg11Trp mutation showed reduced levels of UBA5 protein compared with the wild-type. The mutant p.Arg11Trp UBA5 protein shows reduced ability to activate UFM1. Conclusion: This report expands the phenotypical spectrum of UBA5 mutations to include fatal peripheral neuropathy.